Islamic Education and Intercultural Competence: Promoting Religious Literacy in Multicultural Societies - Ahyar Rasyidi (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2024)
This study explores the contribution of Islamic education to the development of intercultural competence and religious literacy within multicultural societies. Employing a qualitative library research methodology, the study analyzes scholarly literature on intercultural education, Islamic pedagogy, religious literacy, and multicultural learning. The findings demonstrate that Islamic educational principles encourage mutual respect, tolerance, dialogue, and peaceful coexistence through values derived from the Qur'an and Sunnah. Integrating intercultural competence into Islamic education enables students to appreciate cultural diversity while maintaining a strong Islamic identity. The study proposes an Intercultural Islamic Education Framework that emphasizes empathy, critical reflection, intercultural communication, and ethical engagement across religious and cultural boundaries. The novelty of this research lies in synthesizing contemporary intercultural education theories with Islamic educational philosophy to produce a comprehensive framework for strengthening religious literacy in pluralistic societies